Synthesis and characterization of solution-processable diketopyrrolopyrrole (DPP) and tetrathienothiophene (TTA)-based small molecules for organic thin film transistors and organic photovoltaic cells. (October 2016) - Vegiraju, Sureshraju; Hsieh, Cheng-Ming; Huang, Deng-Yi; Chen, Yen-Chia; Priyanka, Pragya; Ni, Jen-Shyang; Esya, Firdausy Amalina; Kim, Choongik; Yau, Shueh Lin; Chen, Chih-Ping; Liu, Cheng-Liang; Chen, Ming-Chou
Abstract: A series of new acceptor-donor-acceptor type conjugated small molecules with alkylated tetrathienoacene as donor and diketopyrrolopyrrole as acceptor moieties has been synthesized and characterized for solution-processed organic thin film transistor and organic photovoltaic applications. To investigate the effect of elongated conjugation on this system, thiophene and bithiophene units were systematically incorporated between the central core and end capped unit. In addition, the effect of alkyl chain substitution on diketopyrrolopyrrole was also examined. The thermal, optical, and electrochemical properties of these new molecules were investigated. The highest hole mobility of organic thin film transistor devices utilizing the solution sheared thin films of these compounds as an active layer is 1.0 × 10 −1  cm 2  V −1  s −1 . Whereas organic photovoltaic cells based on these new molecules exhibited the power conversion efficiencies as high as 2.9% when blends with [6, 6]-phenyl-C71 -butyric acid methyl ester. These performances are strongly correlated with their thin film morphologies. Highlights: Five new soluble DPP-TTA based small molecules were designed and synthesized. The structure-property relationships were systematically examined. The highest hole mobility and PCEs were up to 1.0 × 10 −1  cm 2  V −1  s −1, and 2.9%.